2013
DOI: 10.1159/000350400
|View full text |Cite
|
Sign up to set email alerts
|

Esophagitis with Eosinophil Infiltration Associated with Congenital Esophageal Atresia and Stenosis

Abstract: Background: The esophagus is physiologically devoid of eosinophils, so their presence would suggest some underlying pathology. The prevalence of eosinophilic esophagitis (EoE) has steadily increased in Western countries. Previous studies have described EoE in association with congenital esophageal atresia (CEA), which is the most common congenital anomaly of the esophagus. However, the association remains unclear. Methods: We performed a retrospective histological analysis examining for eosinophil infiltration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 14 publications
3
25
0
2
Order By: Relevance
“…In relation to the clinical presentation, this study found a significantly higher incidence of GERD symptoms, such as vomiting and dysphagia, among patients with EoE compared to those without EoE. 6,18,22 As it is known in EoE, in all series, associated atopy was frequent (Dhaliwal: 50%; Batres: 66%; Gorter: 50%). 3,18,23 A normal endoscopy, linear furrows, edema, and white exudates were described as endoscopic findings.…”
Section: Esophageal Atresia and Eosinophilic Esophagitismentioning
confidence: 62%
See 1 more Smart Citation
“…In relation to the clinical presentation, this study found a significantly higher incidence of GERD symptoms, such as vomiting and dysphagia, among patients with EoE compared to those without EoE. 6,18,22 As it is known in EoE, in all series, associated atopy was frequent (Dhaliwal: 50%; Batres: 66%; Gorter: 50%). 3,18,23 A normal endoscopy, linear furrows, edema, and white exudates were described as endoscopic findings.…”
Section: Esophageal Atresia and Eosinophilic Esophagitismentioning
confidence: 62%
“…3,18,23 A normal endoscopy, linear furrows, edema, and white exudates were described as endoscopic findings. 18,21,22 Multiple biopsies of both the proximal and distal parts of the anastomosis are recommended for EoE diagnosis. 19 In EA, anastomotic stricture occurs in 5-15% of patients, mainly in the first year of life.…”
Section: Esophageal Atresia and Eosinophilic Esophagitismentioning
confidence: 99%
“…Like the infantile form of FPIAP, these patients presented with rectal bleeding as the major and often only clinical manifestation. Apart from primary eosinophilic gastrointestinal diseases, eosinophil accumulation in the colon is a common feature of a variety of conditions, including inflammatory bowel disease, enteric infections, parasitic manifestations, drug reactions, and vasculitis [23,24,25,26]. …”
Section: Discussionmentioning
confidence: 99%
“…Respecto a la clínica, en este mismo estudio, la incidencia de síntomas de ERGE, como vómitos y disfagia, fue significativamente más alta en pacientes con EEo comparada al grupo sin EEo. 6,18,22 Como es conocido en EEo, en todas las series, fueron frecuentes las condiciones atópicas asociadas (Dhaliwal: 50%; Batres: 66%; Gorter: 50%). 3,18,23 Los hallazgos endoscópicos descritos fueron endoscopía normal, surcos lineales, edema y exudados blanquecinos.…”
Section: Atresia De Esófago Y Esofagitis Eosinofílicaunclassified
“…3,18,23 Los hallazgos endoscópicos descritos fueron endoscopía normal, surcos lineales, edema y exudados blanquecinos. 18,21,22 Para el diagnóstico de EEo, se recomiendan múltiples biopsias, tanto proximal y distal a la anastomosis. 19 En AE, la estenosis de la anastomosis ocurre en 5-15%, principalmente, en el primer año de vida.…”
Section: Atresia De Esófago Y Esofagitis Eosinofílicaunclassified